ANALYSIS OF PERFORMANCE MEASUREMENT SYSTEM USING COMPETENCY-BASED BALANCES SCORECARD (A STUDY IN BANJARMASIN STATE POLYTECHNICS) - Agus Pebrianto; M. Wahyu Wardhana; Rika novyanti (Ekonomi & Bisnis, 2015)
Abstract The purpose of this study is to analyze performance based on competency using Balance Scorecard which is measured by four perspectives : College Financial perspective, customer perspective (which divided into three parts : students, stakeholders and graduates), college internal perspective, and learning and growth process perspective. It is expected that this research would lead into development process of the college, and find out the weaknesses or strengths of college organization which would give impact to the increase of college’s performance. This is a quantitative descriptive research. Total amount of population in this research is 208 people, which consists of students from grade 5 of business administrative. The population is chosen in consideration that they have experienced the longest term of learning process. Samples are taken from 4 classes which includes 106 students. Graduates are chosen from those who have been graduates and have at least 3 years working experience, that make 102 people, meanwhile employers are represented by 33 lecturers in Banjarmasin State Polytechnic, and stakeholders are chosen from both government institution and non government institution that makes 27 institutions. Those institutions are chosen by graduates recommendation. The result of reliability test of college financial perspective, customer perspective, university internal perspective and innovation and learning process perspective shows the value more than 0.6 alpha cronbach and it makes all of variables reliable. The average score of financial perspective is 3.514 and it shows that financial condition of the college is in good state, The average score of customer perspective is 2.947 which gives fair condition, the average score of stakeholders perspective is 3.418 that is in good state, and the average score of graduates is showing good state as shown in 3.119 point. College internal process perspective has the average score of 2.753 point and shows fair condition. Learning and growth perspectives average score is 2.929, shows fair condition. Keywords : Balanced Scorecard, Financial Perspective, Customer Perspective, Internal Process Perspective, Learning and Growth Perspective, College Performance